SCALP COMPLICATIONS OF CRANIOFACIAL SURGERY: A COMPREHENSIVE SYSTEMATIC REVIEW - Nur Afiati, Shabrina; Marini, Dini; Sendikamas Hernawan, Lucky (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 21 articles, whereas the results of our search on SagePub get 87 articles, on Google Scholar 2350 articles. Records remove before screening are 1983, so we get 475 articles fos screening. After we screened based on record exclude, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: For craniofacial surgery, understanding the surgical anatomy, identifying risk factors, adequate surgical planning, and interdisciplinary cooperation between neurosurgeons, plastic surgeons, and the interdisciplinary team are essential to prevent and treat scalp complications.